2017 IEEE 47th International Symposium on Multiple-Valued Logic (ISMVL) 2017
DOI: 10.1109/ismvl.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

On the Interval of Boolean Strong Partial Clones Containing Only Projections as Total Operations

Abstract: A strong partial clone is a set of partial operations closed under composition and containing all partial projections. Let X be the set of all Boolean strong partial clones whose total operations are the projections. This set is of practical interest since it induces a partial order on the complexity of NP-complete constraint satisfaction problems. In this paper we study X from the algebraic point of view, and prove that there exists two intervals in X , corresponding to natural constraint satisfaction problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the principal motivation was to obtain dichotomy theorems for CSP-like problems incompatible with existential quantification, and the explicit connection to fine-grained time complexity of CSP was not realised until later by Jonsson et al [36]. However, continued advancements in understanding this inclusion structure revealed that even severely restricted classes of constraint languages have a very complicated structure [18,40]. In particular, it is known that any finite language Γ can be characterized only using an infinite number of partial polymorphisms [41]; in fact, for any finite set of purely partial polymorphisms 𝐹 , the language Γ = Inv(𝐹 ) contains 2 2 Θ(𝑛) relations of arity 𝑛, as opposed to finite languages Γ which can qfpp-define only 2 𝑛 𝑂 (1) relations of each arity.…”
Section: Related Workmentioning
confidence: 99%
“…However, the principal motivation was to obtain dichotomy theorems for CSP-like problems incompatible with existential quantification, and the explicit connection to fine-grained time complexity of CSP was not realised until later by Jonsson et al [36]. However, continued advancements in understanding this inclusion structure revealed that even severely restricted classes of constraint languages have a very complicated structure [18,40]. In particular, it is known that any finite language Γ can be characterized only using an infinite number of partial polymorphisms [41]; in fact, for any finite set of purely partial polymorphisms 𝐹 , the language Γ = Inv(𝐹 ) contains 2 2 Θ(𝑛) relations of arity 𝑛, as opposed to finite languages Γ which can qfpp-define only 2 𝑛 𝑂 (1) relations of each arity.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, this theorem is difficult to apply in practice since it requires a good understanding of the structure of the closed sets pPol(Γ) for all possible choices of Γ. Despite advances made by several different researchers [12,13,35,51], no such classification is known even for Boolean Γ, and even less is known for Γ such that SAT(Γ) is NP-hard. Hence, we propose a method inspired by the rich algebraic toolbox developed for studying the classical complexity of CSP: does the SETH-hardness of SAT(Γ) and CSP(Γ) only depend on the identities satisfied by the partial polymorphisms of Γ?…”
Section: Theorem 1 Let γ and ∆ Be Finite Constraint Languages Over A ...mentioning
confidence: 99%
“…This problem was referred to as the easiest NP-complete SAT problem and was later generalized to a broad class of finite-domain CSPs [32]. However, continued advancements in understanding this inclusion structure revealed that even severely restricted classes of constraint languages had a very complicated structure [12,35]. In a similar vein of negative results it was also proven that (1) pPol(Γ) cannot be generated by any finite set of partial operations whenever Γ is finite and SAT(Γ) is NP-hard, and (2) if P is a finite set of partial operations such that Inv(P)-SAT is NP-hard, then any pp-definable relation over Inv(P) can be transformed into a pp-definition using only a linear number of existentially quantified variables [37].…”
Section: Related Workmentioning
confidence: 99%